Building Students’ Islamic Characters through Information, Communication dan Technology Literacy - Eka Sartika; Suparjo Suparjo; Ihsan Nul Hakim; Dadan Supardan (Institut Agama Islam Negeri (IAIN) Curup, 2018)
In today’s digital world, technology has contributed to an expanded understanding of literacy. Besides having literacy skills, today’s students – millennials - also need technology skills for communicating, investigating, accessing, and using information, thinking critically about messages inherent in new media. Teachers and staff development need to learn the use of technology as well as guiding and opening the students’ perspective where the technology will help them to support the Muslim world. The use of ICT is not only to create the generation with the advanced knowledge in technology but also to have the Islamic character in the future. It is bringing about new opportunity for educators, because it can provide powerful support to educational innovation in creating future generation with Islamic characters. In short, this article is mainly about how the convergence of both literacy instruction and ICT in staff development can help in promoting future generation with Islamic characters. Keywords: Students and teachers, ICT literacy, Islamic Characteremotion